Incidental Findings Following Dental Implant Procedures in the Mandible: A New Post-Processing CBCT Software Analysis - Garrote, Marcel da Silva; Alencar, Ana Helena Gonçalves de; Estrela, Cyntia Rodrigues de Araújo; Estrela, Lucas Rodrigues de Araújo [UNESP]; Bueno, Mike Reis; Guedes, Orlando Aguirre; Estrela, Carlos (MDPI, 2024)
Background/Objectives: The aim of this study was to evaluate incidental findings in the mandible after the placement of dental implants using a new cone–beam computed tomography (CBCT) software. Methods: The initial sample consisted of 2872 CBCT scans of patients of both sexes. The parameters evaluated in this study were the location of the implants in the mandible, implant length, anatomical relationship of the implant with the mandibular canal, presence or absence of damage to the adjacent teeth, presence or absence of implant fractures, and presence or absence of bone support. Fisher’s exact test was performed to compare the variables. The significance level was set at p = 0.05. Results: Out of 2872 CBCT scans, 214 images of patients with an average age of 44.5 years were included. The most frequent location of the implants was the posterior region (93.5%), with 54% of the implants having a length between 9 and 14 mm. It was found that 92% of the implants were positioned above the mandibular canal. Damage to adjacent teeth was observed, with no correlation with the implant positioning (p = 1.000). In 100% of cases of implants in the anterior region, there was bone support. Fracture was observed in 1.7% of implants with a length between 9 and 14 mm. Conclusions: The installation of implants in the mandible occurs more frequently in the posterior region, with a high presence of bone support and a low incidence of damage to adjacent teeth, anatomical structures, and fractures.
Keywords: cone–beam computed tomography; dental implant; diagnosis; incidental findings